Building New Hearts: A Review of Trends in Cardiac Tissue Engineering. Issue 11 (7th October 2014) - Taylor, D. A.; Sampaio, L. C.; Gobin, A.
<x xml:space="preserve">Abstract</x> Cardiovascular disease (CVD) is the number one cause of death in the United States. However, few treatments for CVD provide a means to regain full cardiac function with no long‐term side effects. Novel tissue‐engineered products may provide a way to overcome the limitations of current CVD therapies by replacing injured myocardium with functioning tissue or by inducing more constructive forms of endogenous repair. In this review, we discuss some of the factors that should be considered in the development of tissue‐engineered products, and we review the methods currently being investigated to generate more effective heart valves, cardiac patches and whole hearts.